LEGAL PROTECTION OF CITIZENS' HEALTH RIGHTS COUNTRIES AFFECTED ON MEDICAL WASTE DISPOSAL COVID-19 - Dwiky Maulana Akbar; Nouratama Anugerah Nandiyani; Muhammad Hafidz Rafiansyah (Universitas Islam Lamongan, 2022)
Abstract Every citizen has the right to health and a good environment. The increasing medical waste during the pandemic becomes the government's responsibility in such waste management. However, in practice, medical waste handling cannot be properly resolved. It is detrimental to residents, especially those who live around medical waste disposal. The government has the authority and responsibility to protect, respect, and provide benefits to its citizens. This study was conducted by analyzing the legal norms in the applicable laws and regulations, which was related to the existence of the legal issues that will be examined in the study. From this study, it can be concluded that the government contributes to medical waste management and the right to a good and healthy environment according to the constitution's mandate.